International connections within the national government: Brazilian public legal careers and international circulation (2008-2018) - Engelmann, Fabiano (Crime, law and social change, 2023)
Taking into account the relation between the international circulation of legal elites and the legitimization of institutional models in Brazil, this study comparatively analyzes international leaves of three categories of legal careers between 2008 and 2018: Federal prosecutors, attorneys for Brazil and federal agencies, and federal commissioners. Analysis of the international destinations of these categories allowed us to identify associations established with foreign agencies that disseminate different models of law and contribute to the reinforcement of autonomous corporations in the national space. Our data is built from the mapping of cooperation networks that connect Brazilian prosecutors, attorneys for Brazil and federal agencies, and commissioners with their counterparts in the United States and in international organizations. These connections have contributed to the strengthening of apolitical protagonism of these categories in the Brazilian legal space in recent decades.